Sustainable surface modification of Ti-alloy using powder mixed in bio-dielectrics through micro-electrical discharge coating process. (15th August 2022) - P., Kiran; Mohanty, Shalini; Das, Alok Kumar
Abstract: The present work explores the potential applications of sustainable micro-electrical discharge coating (μ-EDC) process for surface modification of micro-components using solid lubricating powder mixed in bio-oil (Jatropha and Neem oil) as a dielectric medium. The surface modification was carried out on Ti-alloy work piece by setting the voltage and duty factor at different levels. Different characterization technique was followed to evaluate the micro-hardness, surface roughness, and coating layer thickness of the modified surfaces. The analysis of results are presented for the individual oil and powder mixed oil. For Jatropha, the maximum micro-hardness obtained is 642.43 HV0.1 (128%, 274.02 HV0.1 for base material), average surface roughness (Ra ) ranges from 0.54 μm to 1.83 μm; whereas for neem oil, the maximum obtained micro-hardness 592.90 HV0.1, Ra range: 0.78 μm–1.64 μm. When the above oils were mixed with MoS2 powder, the obtained results were further enhanced. The maximum micro-hardness obtained were 543.75 HV0.1 and 712.43 HV0.1, and Ra ranges from 0.47 μm to 1.39 μm, and 0.43 μm–1.35 μm, for Jatropha+MoS2 and neem+MoS2, respectively. The transfer of tool and dielectric materials is affirmed through EDX plots. Graphical abstract: Image 1 Highlights: Novel environment friendly and sustainable coating method for solid lubrication in miniature components. Conversion of bio-oils (Neem and Jatropha) to bio-dielectrics which can be used for micro-electrical discharge coating. Among all bio-dielectrics, Neem + MoS2 produces the best hardness (712.43 HV) and minimum roughness profiles (0.43 μm). Replacement of conventional synthetic dielectric by proposed bio-dielectrics without disturbing the ecological balance.